Experiment study on surface integrity in end milling of hastelloy C-2000 superalloy - Norhaida, Ab Razak; Rahman, Md Mustafizur; Kadirgama, Kumaran (Universiti Malaysia Pahang, 2013)
This paper presents an experimental study of surface integrity in end milling of Hastelloy C-2000. The experiment was carried out using two different cutting inserts under wet conditions –namely Physical Vapor Deposition (PVD) coated carbide with TiAlN and uncoated carbide. Design of experiment (DOE) was implemented with Box-Behnken design. The surface integrity of workpiece was analyzed through scanning electron microscope (SEM) and chemical element changes were inspected by energy dispersive X-ray (EDX) test. The surface integrity of Hastelloy C-2000 was better when machining with coated carbide compare to uncoated carbide cutting insert mainly due to coating layer of coated carbide which actedas protecting layer to the cutting tool insert. Surface defects such as feed marks, surface tearing, plucking, cracking and adhered chips were found during machining process. The chemical element changes happened due to the adhesion and diffusion mechanism which were identifyusing SEM and EDX.